The Impact of General Expenditure on the Tourism Sector in Iraqfor the Period (2003- 2018) - Al- Shaibani, Mohammed Abd Ali Jassim; Al- Jubouri, Mohammed Hussein Kadhim; Al- Khafagy, Haider Eidan Kareem (International Journal of Psychosocial Rehabilitation, 2020)
The tourism sector in Iraq has not received attention and concern by official and interested parties in a manner commensurate with the importance and effectiveness of this sector, because of the advantages of the country in terms of tourism of various kinds particularly that Iraq has gone through several wars and these wars are almost simultaneous with each other. However, these wars have drained the budget of the state; in addition, Iraq is one of the oil countries that are depended on financing its economy mainly on exporting oil. Consequently, this has resulted in the emergence of a problem that hinders tourism development and it is embodied in the great neglect of the tourism sector and the absence a serious attempt by those who are involved in the tourism activity to create actual tourism development that could result in direct and indirect economic effects that contribute to supporting the Iraqi economy, therefore, it is necessary to shed light on this problem and trying to tackle it radically by studying the impact of the general expenditure on the tourism sector, as this expenditure can lead to tourism development in Iraq and trying invest it in a way that reflects positively on the Iraqi economy, and through the use of the standard methods which are represented by unit root testing and joint integration testing and self- regression. The current study concluded that the chain was unstable and settled at the first difference, and the study also found there is a negative relationship between the general expenditure and the tourism sector due to the negative impact of indirect general expenditure on the tourism sector eliminates the direct positive impact.